Reconstruction of Local Knowledge in Science Learning: A Case Study of the Palm Sugar Making Process in Coastal Areas - Fitri April Yanti; Rendy Wikrama Wardana; M Anas Thohir (UIN Fatmawati Sukarno Bengkulu, 2025)
Local context-based science learning is an effective approach to improve students relevance and understanding. This research aims to reconstruct local knowledge of coastal communities related to the process of making palm sugar as a source of science learning. The research method uses a descriptive-qualitative approach. Data were collected through in-depth interviews, field observations, and scientific literature reviews. Furthermore, the data were analyzed through triangulation to produce a scientific interpretation of the traditional practice. The results of the study indicate that the process of making palm sugar reflects the principles of sustainability, utilization of renewable energy, and natural preservation. In addition, the integration of science concepts with business and conservation aspects enriches the relevance of learning for students. It can be concluded that the reconstruction of local knowledge is able to support the preservation of local culture and ecosystems while increasing students understanding of applicable science. The contribution of this study to science is to create a sustainable learning approach, relevant to everyday life, and support the preservation of local wisdom in modern education. This integration provides new opportunities to improve scientific literacy in coastal areas by harmoniously connecting traditional knowledge and science.